The Changing Face of Inflammatory Bowel Disease: Etiology, Physiopathology, Epidemiology - Giovanni Clemente Actis (Iranian Journal of Colorectal Research, 2016)
Context The term inflammatory bowel disease (IBD) classically includes ulcerative colitis (UC) and Crohn’s disease (CD). An abnormally increased mucosal permeability seems to underlie UC, whereas CD is thought to be the result of an immune deficiency state. Evidence Acquisition While these phenomena may well be labeled as genetic factors, the environment has its role as well. Drugs (chiefly, antibiotics and non-steroidal anti-inflammatory molecules, with proton pump inhibitors recently joining the list) and smoking habits are all being scrutinized as IBD causative factors. Results Once almost unknown, the prevalence of IBD, in the Eastern World and China, is now increasing by manifold, therefore arousing warning signals. Conclusions A multidisciplinary approach will soon be necessary, to face the tenacious behavior of IBD, on a global perspective.